2018
DOI: 10.15261/serdj.25.47
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Selective Concentration of Lycopene <i>Z</i>-isomers from Tomato Pulp by Supercritical CO<sub>2</sub> with Co-solvents

Abstract: This study aimed to efficiently separate and concentrate lycopene Z-isomers from tomato pulp using supercritical CO 2 (SC-CO 2). The separation relies on the different solubility of (all-E)-lycopene and the Zisomers. Total lycopene recovery using SC-CO 2 at 50 °C and 30 MPa for 1 h was extremely low (1.2%). Thus, before the separation test, an optimal co-solvent was selected from water, organic chemicals, and edible vegetable oils; hazelnut oil, which had the highest lycopene recovery (21.6%), was adopted. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The extraction of lycopene isomers from the samples was carried out using acetone, according to a previously described method 9,46 . Unless specifically mentioned, all procedures were conducted at room temperature, and light exposure was kept to a minimum throughout the extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of lycopene isomers from the samples was carried out using acetone, according to a previously described method 9,46 . Unless specifically mentioned, all procedures were conducted at room temperature, and light exposure was kept to a minimum throughout the extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in recent years, there has been increased demand for the use of safe and sustainable solvents such as ethanol and supercritical CO 2 (SC-CO 2 ) for the processing of food components including carotenoids, i.e., environmentally benign processing using sustainable solvents is a topic of growing interest in both the research community and the food industry because of the growing awareness of the impact of solvents on energy usage, pollution, and their contribution to climate change and air quality [15,16,17]. However, since (all- E )-carotenoids have very low solubility in ethanol and SC-CO 2 [18,19,20,21], toxic organic solvents are used in many cases. Very recently, several studies demonstrated that Z -isomerization of carotenoids induces alteration in physicochemical properties, such as crystallinity and solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is believed that because lycopene Z-isomers are more soluble in bile acid micelles than the all-E-isomer, they are preferentially incorporated into enterocytes and efficiently form chylomicrons [21,22]. Indeed, very recently, several reports showed that the solubility of lycopene in oils, organic solvents, and supercritical CO 2 (SC-CO 2 ) was significantly improved by Z-isomerization [28][29][30][31][32]. However, Richelle et al [33] showed by human oral-dosing tests that the (9Z)-and (13Z)-isomers were less efficiently absorbed than the 5Zand all-E isomers or were converted into 5Z-and all-E isomers.…”
Section: Lycopenementioning
confidence: 99%
“…In vitro experiments with Caco-2 cells showed that carotenoid transport decreased in the following order: β-carotene ≈ α-carotene (50% inhibition) > β-cryptoxanthin ≈ lycopene (20% inhibition) > lutein: zeaxanthin (1:1) (7% inhibition) [49]. Because carotenoid Z-isomers have higher solubility than the all-E-isomers [28][29][30][31][32], they can incorporate into bile acid micelles more efficiency [21,22]. Therefore, it is considered that Z-isomers of β-carotene have lower transport efficiency in Caco-2 cell than the all-E-isomers [13].…”
Section: β-Carotenementioning
confidence: 99%